Bridge deformation monitoring with single frequency GPS augmented by pseudolites - Cosser, Emily (2005)
Bridges are an important part of the infrastructure of both road and rail networks. As bridge stocks age it is becoming increasing important to monitor their health and predict their lifespan. Current health assessment methods of visual inspection have many drawbacks and so non-destructive evaluation methods such as GPS are becoming more important.